Clinical Outcomes and Rotational Correction of First Metatarso-Cuneiform Fusion With First Metatarsal to Second Cuneiform Fixation - Tonya W. An MD; Robert Fuller BA; Lavan Rajan MS; Agnes Cororaton BS; Matthew S. Conti MD; Jonathan T. Deland MD; Scott J. Ellis MD (Foot & Ankle Orthopaedics, 2022)
Background: The modified Lapidus procedure (first metatarso-cuneiform fusion) is a powerful technique for correcting triplanar deformity in hallux valgus. Although traditionally fixed with cross-screws (CS), growing awareness of intercuneiform stability and pronation deformity has led to fixation using a plate and first metatarsal–second cuneiform (1MT-2C) screw fixation (PS). We investigated Lapidus patient cohorts using CS vs PS fixation to understand patient-reported outcomes, angular and rotational correction, and complication rates. Methods: We retrospectively reviewed cases of modified Lapidus for hallux valgus by a single surgeon. Patients were divided into CS or PS groups according to fixation. All patients had preoperative Patient Reported Outcome Measurement Information System (PROMIS) scores and minimum 12 months of follow-up. PROMIS scores in 6 key domains were compared within and between groups. Radiographic assessment of hallux valgus angle and intermetatarsal angle were performed on pre- and postoperative XR. Pronation of the first ray was measured on pre- and postoperative weightbearing computed tomography. Results: We compared 42 patients with PS fixation to 43 with CS fixation. Both groups had significant improvement in hallux valgus angle and intermetatarsal angle ( P < .001), with no difference between groups. PS patients experienced a greater correction of first metatarsal pronation, an average reduction of 11 degrees, compared to 8 degrees in the CS group ( P < .039). Both cohorts experienced improvement in PROMIS physical function, pain interference, pain intensity, and global physical function. There were no differences in PROMIS score improvements between the cohorts. The CS group started weightbearing at 6 weeks vs 3.6 weeks for the PS group. Complication and revision rates were similar. Conclusion: A plate and 1MT-2C screw fixation provides safe, robust fixation of Lapidus procedure and prevents instability through the intercuneiform joint. We observed similar improvement in PROMIS compared with patients treated with cross-screws. Complications did not increase despite the PS group weightbearing much earlier. PS patients achieved greater first ray rotational correction. Level of Evidence: Level III, retrospective cohort study.